Application of Statistical Quality Control in Monitoring Concrete Compressive Strength - William Bagita Samuel; Eswan Eswan; Wahyu Mahendra (Journal of Applied Sciences, Management and Engineering Technology, 2026)
Concrete is a primary material in construction, directly influencing structural strength and stability. Therefore, quality control, particularly of compressive strength, is essential. This study evaluates the planned concrete strength of f’c 30 MPa used in the Presidential Parking Building Project at Indonesia’s new capital, employing a Statistical Quality Control (SQC) approach. The main objective is to assess the stability of concrete quality and the effectiveness of various control chart methods in statistically monitoring the production process. A total of 32 compressive strength tests were conducted at 7 and 28 days, each involving three specimens. Five control chart methods were applied: X̄, R̄, S̄, Moving Range (MR), and Moving Average (MA), based on SNI 1974:2011 standards. Results show that the X̄ chart indicates the average compressive strength remains within control limits, suggesting process stability. R̄ and S̄ charts confirm controlled variation among samples, while MR charts reveal minor short-term fluctuations. MA charts successfully capture subtle trends without indicating significant process shifts. Overall, the concrete production process is statistically in-control. The combined use of these five control charts provides a comprehensive view of concrete quality; covering average, variation, and trend, and serves as a foundation for continuous quality improvement.